Social Issues in Military Bulletin The War Diary in 1918 - Stanojević, Saša D. (Sociološki pregled, 2019)
The subject of the paper are social topics represented in War Diary in 1918. By analyzing the content, it was noted that along with the war reports, this ofcial military bulletin also published articles on current social issues. Viewed through the sociological aspect, they oﬀer the possibility of a further reconstruction of the state of Serbian society in exile. It can be concluded that apart from the basic function of providing information and maintaining morals, War Diary was in the service of popularizing the idea of Yugoslavism, with increasing intensity as the last war year was coming to an end. Keywords: War Diary, 1918, society.